Bone’s responses to different designs of implant-supported fixed partial dentures - Rungsiyakull,C. (Springer Verlag, 2015)
© 2014, Springer-Verlag Berlin Heidelberg. This paper explores the biomechanics and associated bone remodeling responses of two different abutment configurations, namely implant–implant-supported versus tooth–implant-supported fixed partial dentures. Two 3D finite element analysis models are created based upon computerized tomography data. The strain energy density induced by occlusal loading is used as a mechanical stimulus for driving the bone remodeling. To measure osseointegration and stability during healing, a resonance frequency analysis is conducted. At the second premolar peri-implant region, overloading resorption around the neck of implant is identified in both the models over the first 12 months. Stress-shielding around the edentulous region is also observed in both the models with a greater resorption rate found in the implant–implant case. The remodeling and resonance frequency analyses reveal that the tooth–implant scheme offers a higher degree of osseointegration. The remodeling procedure is expected to provide prosthodontists with a modeling tool to assess possible long-term clinical outcomes.